Pregunta

(c) Let \( f(x)=6 x^{3}+19 x^{2}+2 x-3 \) be a polynomial. Find all rational roots of the equation \( f(x)=0 \).

Ask by Sanders Williams. in Zambia
Feb 24,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

The rational roots of the equation \( f(x) = 6x^{3} + 19x^{2} + 2x - 3 = 0 \) are: - \( x = -3 \) - \( x = \frac{1}{3} \) - \( x = -\frac{1}{2} \)

Solución

To find the rational roots of f(x) = 6x³ + 19x² + 2x − 3, we can use the Rational Root Theorem. This theorem tells us that any rational root, in lowest terms p/q, must have p as a divisor of the constant term (−3) and q as a divisor of the leading coefficient (6). Step 1: List the possible values for p and q.   Divisors of −3 (p): ±1, ±3   Divisors of 6 (q): ±1, ±2, ±3, ±6 Step 2: Write down the possible rational roots as p/q:   Possible roots: ±1, ±3, ±1/2, ±3/2, ±1/3, and ±1/6. Step 3: Test these candidates by substituting them into f(x). Testing x = −3:   f(−3) = 6(−3)³ + 19(−3)² + 2(−3) − 3     = 6(−27) + 19(9) − 6 − 3     = −162 + 171 − 6 − 3     = 0 So, x = −3 is a root. Step 4: Factor the polynomial using the root x = −3. Since x = −3 is a root, (x + 3) is a factor. Divide f(x) by (x + 3) using synthetic division. Set up synthetic division with the coefficients 6, 19, 2, −3 and use −3:     -3 | 6  19  2  −3         -18  -3  3       ------------------        6  1  −1  0 The division gives a quotient of 6x² + x − 1, so:   f(x) = (x + 3)(6x² + x − 1). Step 5: Solve the quadratic equation 6x² + x − 1 = 0. Use the quadratic formula:   x = [−b ± √(b² − 4ac)] / (2a), where a = 6, b = 1, and c = −1. Calculate the discriminant:   b² − 4ac = 1² − 4(6)(−1) = 1 + 24 = 25. Now, solve for x:   x = [−1 ± √25] / (2*6)   x = (−1 ± 5) / 12 This gives two roots:   x = (4)/12 = 1/3   x = (−6)/12 = −1/2 Step 6: List all the rational roots. The rational roots of the equation are:   x = −3, x = 1/3, x = −1/2.

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Extra Insights

To find the rational roots of the polynomial \( f(x) = 6x^3 + 19x^2 + 2x - 3 \), we can use the Rational Root Theorem. This theorem states that any rational solution of \( f(x) = 0 \) must be of the form \( \frac{p}{q} \), where \( p \) is a factor of the constant term (-3), and \( q \) is a factor of the leading coefficient (6). The factors of -3 (the constant term) are \( \pm 1, \pm 3 \), and the factors of 6 (the leading coefficient) are \( \pm 1, \pm 2, \pm 3, \pm 6 \). Thus, the possible rational roots are: \[ \pm 1, \pm 3, \pm \frac{1}{2}, \pm \frac{3}{2}, \pm \frac{1}{3}, \pm \frac{3}{3} = \pm 1, \pm \frac{1}{6} \] Now we will test these potential roots in \( f(x) \) to find any valid rational roots. 1. Testing \( x = 1 \): \[ f(1) = 6(1)^3 + 19(1)^2 + 2(1) - 3 = 6 + 19 + 2 - 3 = 24 \quad (\text{not a root}) \] 2. Testing \( x = -1 \): \[ f(-1) = 6(-1)^3 + 19(-1)^2 + 2(-1) - 3 = -6 + 19 - 2 - 3 = 8 \quad (\text{not a root}) \] 3. Testing \( x = 3 \): \[ f(3) = 6(3)^3 + 19(3)^2 + 2(3) - 3 = 6(27) + 19(9) + 6 - 3 = 162 + 171 + 6 - 3 = 336 \quad (\text{not a root}) \] 4. Testing \( x = -3 \): \[ f(-3) = 6(-3)^3 + 19(-3)^2 + 2(-3) - 3 = 6(-27) + 19(9) - 6 - 3 = -162 + 171 - 6 - 3 = 0 \quad (\text{root found!}) \] 5. Testing \( x = \frac{1}{2} \): \[ f\left(\frac{1}{2}\right) = 6\left(\frac{1}{2}\right)^3 + 19\left(\frac{1}{2}\right)^2 + 2\left(\frac{1}{2}\right) - 3 = \frac{6}{8} + \frac{19}{4} + 1 - 3 = \frac{3}{4} + \frac{19}{4} + 1 - 3 = \frac{22}{4} + 1 - 3 = \frac{22}{4} + \frac{4}{4} - \frac{12}{4} = \frac{14}{4} \quad (\text{not a root}) \] 6. Testing \( x = -\frac{1}{2} \): \[ f\left(-\frac{1}{2}\right) = 6\left(-\frac{1}{2}\right)^3 + 19\left(-\frac{1}{2}\right)^2 + 2\left(-\frac{1}{2}\right) - 3 = -\frac{6}{8} + \frac{19}{4} - 1 - 3 = -\frac{3}{4} + \frac{19}{4} - \frac{4}{4} - \frac{12}{4} = \frac{-3 + 19 - 4 - 12}{4} = \frac{0}{4} = 0 \quad (\text{another root found!}) \] Now, we have found two rational roots: \( x = -3 \) and \( x = -\frac{1}{2} \). Thus, the rational roots of the equation \( f(x) = 0 \) are: \[ x = -3, \quad x = -\frac{1}{2} \]

preguntas relacionadas

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad